Facial Gender Surgery: Systematic Review and Evidence-Based Consensus Guidelines from the International Facial Gender Symposium. Issue 1 (21st December 2021) - Coon, Devin; Berli, Jens; Oles, Norah; Mundinger, Sol; Thomas, Kate; Meltzer, Toby; Houssock, Carrie; Satterwhite, Thomas; Morrison, Shane; Bailón, Carlos; Tenório, Thiago; Simon, Daniel; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Increasing societal acceptance of transgender people has led to broader availability of gender surgery and rapid growth in transition-related operations. Facial gender surgery aims to modify patients' facial features to be more congruent with their physical expression of gender, reducing gender dysphoria and improving quality of life. Growth in research and technique evolution has not kept pace with growth in clinical volume. Therefore, the first International Facial Gender Symposium was held at Johns Hopkins University in 2019, convening surgeons who perform facial gender surgery to share ideas and assess the state of clinical evidence. Methods: To review the literature on facial gender surgery, the authors developed a search strategy for seven electronic databases (PubMed, PsycINFO, Embase, CINAHL, Web of Science, Cochrane, and Gender Studies) through May of 2019, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses systematic review guidelines. Results: Based on the English language literature and clinical experience, the authors suggest guidelines for screening, management, and appropriate surgical technique for patients undergoing facial gender surgery. They highlight facial gender surgery as a medically necessary intervention and identify shortcomings in current guidelines. Conclusions: Facial gender surgery represents a complex array of craniofacial and soft-tissue procedures that require application of advanced skills and decision-making. Facial gender operations are not cosmetic, are medically necessary, and require development of new CPT codes specific to facial gender surgery. It is imperative to create educational programs and methods to define sufficient training for facial gender surgery surgeons. Research priorities include better procedural outcomes data, more quality-of-life studies, and insight into variation in both patient and procedural subgroups.